Misinformed Speculators and Mispricing in the Housing Market - Chinco, Alex; Mayer, Christopher (Review of Financial Studies, 2016)
This paper examines the contribution of out-of-town second-house buyers to mispricing in the housing market. We show that demand from out-of-town second-house buyers during the mid 2000s predicted not only house-price appreciation rates but also implied-to-actual-rent-ratio appreciation rates, a proxy for mispricing. We then apply a novel identification strategy to address the issue of reverse causality. We give supporting evidence that out-of-town second-house buyers behaved like misinformed speculators, earning lower capital gains (misinformed) and consuming smaller dividends (speculators). Received August 4, 2014; accepted August 28, 2015 by Editor Stefan Nagel.